Carbon footprint of global natural gas supplies to China - Yu Gan (Nature Portfolio, 2020)
The carbon footprints of natural gas supplies at the field level are unclear. Here the authors analysed the GHG intensities of gas supplies from 104 fields and show that their GHG intensities range from 6.2 to 43.3 g CO2eq MJ-1.